Law as a Political Conversation. Critical Notes on El derecho como una conversación entre iguales by Roberto Gargarella (Universidad de San Andres Law Review, 2021)
In this paper we will analyze some aspects of Roberto Gargarella’s recent work, El derecho como una conversación entre iguales. First, we will give an account of the author’s general diagnosis, and then we will briefly describe the regulative ideal of conversation between peers proposed by Gargarella. Next, we will criticize some features of the author’s general diagnosis of democracy, as well as specific aspects of his regulative ideal. Finally, we will conclude with some thoughts.
Keywords: law; politics; conversation